2005
DOI: 10.1007/s11176-005-0491-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Effects in Processes of Corrosion of Metals

Abstract: Mechanochemical effects have been investigated in the processes of corrosion of bent plates of unalloyed and high-alloy steel in aqueous solutions of sulfuric and hydrochloric acids. Special attention was paid to the strain sign effect discovered recently and caused by the existence of a surface stress in solids. The use of the weight method and the hydrogen method of corrosion control has yield well consistent results confirming the existence of the mechanochemical effect of the strain sign even under conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Under external load, it has been generally agreed that the plastic strain will significantly reduce the corrosion resistance by directly enhancing the anodic reaction [7,11,14,16,[21][22][23][24][25][26] while the hydrogen evolution was reported to increase as well [21,22]. Despic et al [11] observed that a negative corrosion potential shifted by up to 30 times, with a marked increase in the anodic current density at the onset of the tensile plastic strain and reached an asymptotic value gradually.…”
Section: Introductionmentioning
confidence: 99%
“…Under external load, it has been generally agreed that the plastic strain will significantly reduce the corrosion resistance by directly enhancing the anodic reaction [7,11,14,16,[21][22][23][24][25][26] while the hydrogen evolution was reported to increase as well [21,22]. Despic et al [11] observed that a negative corrosion potential shifted by up to 30 times, with a marked increase in the anodic current density at the onset of the tensile plastic strain and reached an asymptotic value gradually.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that the total pressure may have an effect on simulating CO 2 corrosion probably because the external pressure will influence the metal's corrosion process and accelerate corrosion rate especially [2][3][4][5]. This theory is related to mechanical-chemical phenomenon reported by Gutman.…”
Section: Theory Basismentioning
confidence: 99%